COMPARATIVE STUDY BETWEEN MULTIPLE CHOICE AND CLOZE-TEST TOWARD STUDENTS READING COMPREHENSION ACHIEVEMENT AT SMK NEGERI 1 TOMBULU - Tiara Kambey; Maikel Sanger; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2023)
This research aims to find out a comparative score between multiple choice and cloze-test toward student’s reading comprehension achievement at SMK Negeri 1 Tombulu. This research used quantitative research with the type of comparative research that used the test method. The subject in this research were the first-grade students of SMK Negeri 1 Tombulu. The data collection technique used two types of tests, first is multiple-choice objective consist of 20 number and second is cloze-test consist of 20 number. The writer used the IBM SPSS Statistics Program and the Independent Sample T-Test formula to analyse the data. The results showed that the average score of students' reading on the multiple choice test was 81.40 while the average score on the cloze-test was 58.00. This value indicates that the multiple choice obtains higher results than the cloze test. It is proved that the significance value of sig. (2-tailed) is <0.001 or has a value of 0.000. That is, sig. value (2-tailed) < 0.05. According to the independent sample t-test, it can be concluded that H0 is rejected and Ha is accepted. This means that the multiple choice test is better to assess students' reading comprehension achievement in first-grade students of SMK Negeri 1 Tombulu.